Plastic Vanitas and Amani Vanitas: Amani-Traces of a Colonial Research Centre, MAARK, Museum am Rothenbaum, Hamburg,Germany 19th September 2019 - April 2020. - Mariele Neudecker (2021)
Emerging from residencies at the Museum of Design in Plastics and Amani, an abandoned post colonial science research centre in Tanzania, the Vanitas works question what constitutes an archive and how responses to it might forge new connections, shedding light on our anthropological heritage, sustainability and our relationship to the environment. This item contains 8 images of the 11 exhibited Amani photoworks, 2 of the 3 exhibited videos and 1 of the 2 stereoscopic photographs. This item documents the inclusion of works made by Neudecker during a research residency at Amani, an abandoned post colonial research centre in Tanzania, once the gem of German colonial science. In this exhibition Neudecker and the other participating artists examine the traces of this colonial and post colonial legacy at Amani. The exhibited works resulting from her Amani research consists of 3 videos, and 11 photographic works, as well as 2 specially commissioned works that take the form of Stereoscopic viewers, Your Head Is Younger Than Your Feet (Blackfly) , and Your Head Is Older Than Your Feet (Mosquito). F unded by the Faculty of Social and Behavioural Sciences at the University of Amsterdam these commissioned works were based on John Raybould's collection of insects developed at Amani and then donated to the Natural History Museum in London. Amani-Traces of a Colonial Research Centre , was a group exhibition curated by Prof Wenzel Geissler from the University of Oslo. Wenzel Geissler co-convened the 2013 workshop in Finse, Norway, on the work of remote Tropical and Arctic research stations, that was the starting point for Neudecker's Vanitas works. Photography : Courtesy of the artist and MAARK. Used with permission. The work is under copyright and may not be used without permission. Use of this repository acknowledges cooperation with its policies and relevant copyright law.